Vascular access specialist teams versus standard practice for catheter insertion and prevention of failure: a systematic review - Peter Carr; Ian Blanco-Mavillard; Miguel Angel Rodríguez-Calero; Ismael Fernandez-Fernandez; Paulo Santos-Costa; Gaizka Parra-García (BMJ Open)
Objective Billions of vascular access devices (VADs) are inserted annually for intravenous therapy worldwide. However, their use is not without challenges. Facilitating the process and enhancing results, hospital authorities have created vascular access specialist teams (VASTs) with advanced competencies in the evaluation, insertion, care and management of VADs. The objective is to compare the effectiveness of VASTs versus standard practice regarding cannulation success and vascular access maintenance in hospitalised adults.Design Systematic review, using the Mixed Methods Appraisal Tool.Data sources We conducted a structured data search on Cochrane Library, MEDLINE, Web of Science, Scopus and EBSCOhost up to 31 May 2023. We did not impose a time limit regarding the date of publication.Eligibility criteria Studies were eligible for inclusion in the review if they were randomised and non-randomised trials and observational studies.Data extraction and synthesis We included studies that described or evaluated the activity of VASTs compared with clinical practitioners. The outcomes analysed were the success of the cannulation and the incidence of associated adverse effects.Results The search strategy produced 3053 papers published between 1984 and 2020, from which 12 were selected for analysis. VASTs are heterogeneously described among these studies, which mainly focus on insertions, frequently for patients with difficult intravenous access. Some patients presented with specific needs or requirement for specific insertion technique or catheter type. Compared with usual practice, these studies indicate that the involvement of a VAST is associated with a higher effectiveness in terms of first attempt insertions and insertion success rates, and a reduction in catheter-associated adverse events. However, meta-analyses confirming this trend are not currently possible.Conclusions It seems apparent that VASTS contribute to improving the health of patients during the administration of intravenous. VASTs seem to increase the effectiveness of VAD insertion and care and reduce complications.PROSPERO registration number CRD42021231259.